Building knowledge across transnational boundaries: Collaboration and friendship in research. (August 2016) - Lund, Ragnhild; Kusakabe, Kyoko; Panda, Smita Mishra; Wang, Yunxian
Highlights: Friendship has contributed to our production of knowledge, how we have created a "relational space", and worked to maintain our friendship. Friendship influences our knowledge production process through providing trust and sense of security. Spending years at the same place has created a space that bonds us, through our experiences of being mothers, students, and co-workers. Chit-chatting and casual touch-base relations are important to maintain the connection. Mutual support has elevated individual performances, and simultaneously strengthened our friendship.